2023
DOI: 10.1039/d2np00075j
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in gut microbiota-associated natural products: structures, bioactivities, and mechanisms

Abstract: Natural products modulate interactions between gut microbiota and host.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…Many natural products (NPs) have been shown to confer advantages for health by modulating the composition of the gut microbiota. Ginseng is a highly esteemed herbal medicine, and ginsenosides, as the primary active constituents of ginseng, have been employed in treating various pathological conditions, including antioxidant, anti-inflammatory, and antitumor . Ginsenoside compound K (CK) is a unique and rare ginsenoside converted from the metabolic transformation of diol-type ginsenosides Rb1 and Rb2 by gut microbiota enzymatic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Many natural products (NPs) have been shown to confer advantages for health by modulating the composition of the gut microbiota. Ginseng is a highly esteemed herbal medicine, and ginsenosides, as the primary active constituents of ginseng, have been employed in treating various pathological conditions, including antioxidant, anti-inflammatory, and antitumor . Ginsenoside compound K (CK) is a unique and rare ginsenoside converted from the metabolic transformation of diol-type ginsenosides Rb1 and Rb2 by gut microbiota enzymatic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…7 This has led to intense activities and interest in the identification, biosynthesis and functions of secondary metabolites (natural products) from the human microbiome, especially in those derived from human commensal bacteria. 8,9…”
Section: Introductionmentioning
confidence: 99%
“…10 Hence, culture-independent genomic approaches, supported by computational algorithms for processing large volumes of genetic information from HMP reference genomes and interfacing with phenotypic data, were explored. 8–17 In this regard, the three commonly pursued approaches are (a) sequence-based metagenome mining, (b) functional genomics and (c) mass spectrometry-based metabolomics analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, LPS from the pathogenic bacteria are dangerous and harmful to human health via the host immune system overactivations, including the induction of metabolic endotoxemia, the promotion of dysglycemia and adipose inflammation, and the impairment of gut barrier function. [6] However, recent studies demonstrated that LPS from the commensal gut microbiota were beneficial for human health and played crucial roles in auto-immunity and immune homeostasis. [7] Structural differences of the commensal gut microbiota-derived LPS are believed to be reasons for the different immunological properties.…”
Section: Introductionmentioning
confidence: 99%